2010
DOI: 10.1016/j.molcel.2010.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd3 and UTX Play a Demethylase-Independent Role in Chromatin Remodeling to Regulate T-Box Family Member-Dependent Gene Expression

Abstract: The stable and heritable H3K27-methyl mark suppresses transcription of lineage-specific genes in progenitor cells. During developmental transitions, histone demethylases are required to dramatically alter epigenetic and gene expression states to create new cell-specific profiles. It is unclear why demethylase proteins that antagonize polycomb-mediated repression continue to be expressed in terminally differentiated cells where further changes in H3K27-methylation could be deleterious. In this study, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
286
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(303 citation statements)
references
References 41 publications
13
286
2
1
Order By: Relevance
“…A demethylase-independent role of JMJD3 has been described in differentiated cells (T-helper 1 cells) in which the epigenetic profile is already established and fulfills another role. Specifically, JMJD3 mediates a functional interaction between T-bet, a T-box transcription factor, and a Brg1-containing switch/sucrose nonfermentable (SWI/SNF) remodeling complex (50). We have confirmed that JMJD3 acts during the active demethylation process of early embryo development, but we are not able to rule out the possibility that JMJD3 also enacts demethylase-independent consequences during embryo development.…”
Section: Discussionmentioning
confidence: 70%
“…A demethylase-independent role of JMJD3 has been described in differentiated cells (T-helper 1 cells) in which the epigenetic profile is already established and fulfills another role. Specifically, JMJD3 mediates a functional interaction between T-bet, a T-box transcription factor, and a Brg1-containing switch/sucrose nonfermentable (SWI/SNF) remodeling complex (50). We have confirmed that JMJD3 acts during the active demethylation process of early embryo development, but we are not able to rule out the possibility that JMJD3 also enacts demethylase-independent consequences during embryo development.…”
Section: Discussionmentioning
confidence: 70%
“…This result is consistent with the recent finding that Jmjd3 functions in control- [19] . Jmjd3 also has demethylase-independent functions: Miller et al [35] reported that Jmjd3 mediates a functional interaction between the lineage-defining T-box transcription factor family member and its target genes. T-box transcription factor family members, such as Brachyury and Tbx5, are critical regulators of cardiac differentiation [36] .…”
Section: Discussionmentioning
confidence: 99%
“…PRC1, in turn, can ubiquitinate lysine 119 of histone H2A, leading to a closing of the chromatin structure [46,189]. Similarly, KDM3A and KDM6 demethylases play a role in chromatin remodeling by linking transcription factors with the SWI/SNF chromatin remodeling complex [190,191]. Since these proteins regulate the chromatin compaction associated with genes involved in carcinogenesis and cell proliferation, mutation or depletion of histone demethylases could interfere with these biological processes.…”
Section: Beyond the Histone Demethylase Functionmentioning
confidence: 99%